The Effect Of Constraint Induced Movement Therapy (Cimt) On Gripping Strength In Stroke Patients At Siti Aisyah Hospital, Lubuklinggau City - Septarini, Cindy; Riyanto, Agus; Fitrizah, Miki Kurnia (Universitas Dehasen Bengkulu, 2023)
Stroke is a serious, life-threatening medical condition in which poor blood flow to the brain leads to cell death. Patients who are suffering from stroke certainly have various kinds of problems, one of which is body weakness (paresis) limitations in grasping. The problem of the research is that there are still many cases of stroke patients with a decrease in grasping strength at Siti Aisyah Hospital, Lubuklinggau City. The purpose of this study is to determine the effect of Constraint Induced Movement Therapy on gripping strength in stroke patients.This study uses a type of quantitative research with a pre-experimental design approach with a one-group pre-test-post test design, namely research carried out for a population group of 60 patients and a sample of 10 patients. The bivariate statistical analysis method used in this study is the Paired T Test.The results of the study obtained the average value of grasping strength before Constraint Induced Movement Therapy, which was 9,150. The results obtained the average value of grasping strength after Constraint Induced Movement Therapy which was 12,950. The results of the bivariate analysis test with the T test showed that there was an effect of Constraint Induced Movement Therapy on grasping strength in stroke patients with a p value = 0,000.The results of the study suggest to provide Constraint Induced Movement Therapy exercises with longer application and are expected to be used to administer Constraint Induced Movement Therapy to stroke patients who experience grasping weakness.